International money and finance - Hallwood, Paul C.; MacDonald, Ronald (Malden, MA : Blackwell, 2000)
Introduction. Some basic concepts in international finance. Spot and forward exchange rates. Income and the balance of payments. Macroeconomics in an open economy. International policy coordination. Purchasing power parity...
Keywords: Finance; Economics; International finance